PENYULUHAN DAN PELATIHAN ICT-ENHANCED TEACHING –LEARNING SEBAGAI MODEL PENGEMBANGAN PROFESIONAL GURU DI KOTA BENGKULU - Azwandi, Azwandi; Harahap, Alamsyah; Syafryadin, Syafryadin (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2019)
The use of  ICT in learning is rarely found particularly in areas with low literacy. Like a high school teacher at Bengkulu City, they do not use ICT in learning, especially they whom  with over the age of 40 years old. The lact of fasilitators  also make difficult to reach innovative  learning with high quality. Thus, It absolutely needs counseling and training on ICT. This training aims not only to give guidance on ICT, but also to move the teachers  for using ICT as a medium of professional learning  in their class routines. This training used the method of  lectures, discussions and practice with the participatns of 20 teachers at Anggut Atas Village, Gading Cempaka District, Bengkulu City on all subjects.  The results of this training indicated  that the use of ICT on learning suach as Mobile-Asissted Language Learning (MALL) ataupun Computer-Assisted Language Learning (CALL) could be received and actualized by the teachers at Anggut  Atas Village, Gading Cempaka District, Bengkulu City. This training can be concluded that implementation of ICT  with the existance of facilitators  are very needed in developing innovative and efficient learning with high quality.